2019
DOI: 10.12788/jhm.3183
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Practice Provider Clinical Fellowship as a Pipeline to Staffing a Hospitalist Program

Abstract: T here is an increasing utilization of advanced practice providers (APPs) in the delivery of healthcare in the United States. 1,2 As of 2016, there were 157,025 nurse practitioners (NPs) and 102,084 physician assistants (PAs) with a projected growth rate of 6.8% and 4.3%, respectively, which exceeds the physician growth rate of 1.1%. 2 This increased growth rate has been attributed to the expectation that APPs can enhance the quality of physician care, relieve physician shortages, and reduce service costs, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Existing literature suggests a lack of standardized postgraduate training in HM-specific competencies for PAs and NPs. 12,13 Further, recently graduating APPs often feel underprepared for clinical practice 14 and undertrained APPs may incur additional costs to HM groups 12 ; under-training may also contribute to turnover. Given these combined results, there may be a role for expanding post- HM groups nationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature suggests a lack of standardized postgraduate training in HM-specific competencies for PAs and NPs. 12,13 Further, recently graduating APPs often feel underprepared for clinical practice 14 and undertrained APPs may incur additional costs to HM groups 12 ; under-training may also contribute to turnover. Given these combined results, there may be a role for expanding post- HM groups nationally.…”
Section: Discussionmentioning
confidence: 99%
“…graduate HM-specific training for APPs. There are already several such postgraduate training programs in existence,12,13 and there is evidence to support that formal HM-specific postgraduate training leads to greater confidence, job satisfaction, and marketability among APPs [12][13][14][15]. These training programs could be further standardized by an accepted accrediting body to ensure graduates meet defined core competencies in HM, similar to those defined for HMphysicians.…”
mentioning
confidence: 99%
“…This practice is consistent with a growing trend toward postgraduate PA hospitalist training to supplement the variable but often limited PA inpatient training during standard graduate education. 2 , 9 Before 2016, and before the introduction of rounding hospitalist PAs, hospitalist physicians were responsible for about 15 patients each day on 1-week (7-day) rotating shifts, Saturday through Friday. In 2016, our PA-physician model started staffing with the first graduated class of PA fellows; the team worked every other week, with the alternate weeks continuing with the physician-only model.…”
Section: Methodsmentioning
confidence: 99%
“…1 PAs are considered a cost-effective means to enhance the reach of hospital patient care. 2 Studies have shown that PAs can be successfully integrated into hospitalist services. 2 - 5 However, the optimal working model for hospitalist services and the PA-physician relationship has not been determined in terms of outcomes, patient safety, and patient satisfaction.…”
mentioning
confidence: 99%
“…Finally, as hospitalist teams have grown to include advanced practice providers (APPs), some programs have established formal teaching programs to address professional development needs of these healthcare professionals. 10,11…”
Section: Beyond Traditional Resident Teaching Teamsmentioning
confidence: 99%